(untitled) (Tábano, 2025)
In this paper, we trace the concept of agencement in the work of Deleuze and Guattari, following its adjustments and modifications from The Anti-Oedipus (1972) to A Thousand Plateaus (1980), passing through Kafka, for a minor literature (1975). Next, we will present the concept of assemblage in Manuel DeLanda, attending to its minimal and extended versions and trying to make explicit its points of contact and tension with the French thinkers. Throughout this overview, we will try to show the genealogy of the concept taken up by DeLanda, as well as the difference between the concerns to which agencements respond and those to which assemblages respond. The transformation of the concept, in this sense, shows a displacement of the centrality of language in favor of an ontology articulated with the empirical and formal sciences, in which the notion of emergence will be central.